Summary proceedings of the twenty-fifth annual meeting of the Board of Governors - International Monetary Fund (Washington D.C. International Monetary Fund, 1970)
These summary of proceedings include statements, or portions of statements, relating to the work of the Fund which were made by the Governors during the Meetings
osc 23/08/2021
Ref
Keywords: International Monetary Fund